Are we operating asymptomatic patients but infected with Covid19? retrospective analysis of patients operated at the Maciel Hospital - Moreira, Emilia; Espinosa, Gabriela; Chinelli, Javier; Laguzzi, Cecilia; Sarries, Florencia; Martínez, Marcia; Ximénez, Valentina; Irigoyen, Virginia; Brandolino, Soledad; Ramírez, Virginia (Cirugía del Uruguay, 2020)
Introduction: Since March 2020, COVID-19 infection was declared a pandemic with consequent impact on the health system. A particular case is the surgery service with the risk linked to transmission by microdrops or pneumoperitoneum. To reduce the risk of contagion, non-oncological coordination surgeries have been suspended. The objective of this study was to assess the proportion of asymptomatic patients at the time of surgery and who developed the disease after surgery. Materials and methods: This is an observational, descriptive and retrospective study. A search was made in the operative descriptions system of the Maciel Hospital, identifying the surgical procedures of all the specialties performed from March 16 to April 16, 2020. Demographic variables, variables related to surgery, complications and respiratory symptoms were recorded. Results: 128 patients were included, on which 165 procedures were performed. 42.2% of the coordination procedures, 52.1% of urgency and 5.5% of emergency were performed. It is highlighted that 73.4% of the patients did not present complications and a mortality of only 7.8% was found. 9 (7.0%) swabs were performed in the period, none of them was positive. Conclusions: COVID-19 infection is linked to an increase in postoperative mortality compared to pre-epidemic mortality, which requires strict triage to minimize risk. We highlight in our center the absence of surgery in asymptomatic patients with the infection.